2012
DOI: 10.1055/s-0032-1309361
|View full text |Cite
|
Sign up to set email alerts
|

Prediction scores in gastrointestinal bleeding: a systematic review and quantitative appraisal

Abstract: Background and study aims: Several algorithms predicting outcomes in acute gastrointestinal bleeding have been developed over the past three decades. These algorithms differ substantially and therefore the aim of the current study was to conduct a systematic review to compare their predictive performance and methodological quality in gastrointestinal bleeding. Methods: A PubMed literature search was performed up to 1 July 2011.?All studies reporting prediction scores in gastrointestinal bleeding were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In UGIB, several prognosis scores were reported (2426) developed and validated in prospective multicenter studies. But these were only designed and validated for patients with UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…In UGIB, several prognosis scores were reported (2426) developed and validated in prospective multicenter studies. But these were only designed and validated for patients with UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, two systematic reviews on the predictive value of risk scores in UGIB patients have been conducted . One review by Stanley concluded that GBS has a higher diagnostic accuracy compared to the cRockall score and could be used for identifying low‐risk patients who can be managed as outpatients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A large systematic review of scores compared the predictive performance and methodological quality of various risk stratification scores in patients with UGIB. 49 Among the preendoscopy scores, the GBS was found to be one of the highest-quality scores and its use was recommended when evaluating the need for intervention. Accumulating evidence suggests that effective and safe outpatient management can be implemented for patients admitted to the hospital with UGIB who are categorized as lowest risk using the GBS (GBS of 0) at presentation.…”
Section: Scores Applied Before Endoscopymentioning
confidence: 99%
“…53 It was subsequently validated in further studies. 49 Taking into account the ability of the GBS to predict the need for treatment, a series of studies have evaluated the ability of the GBS to identify low-risk patients who may be managed as outpatients. Many of these studies found that for patients presenting with UGIB and a GBS of 0, the need for intervention was <1%.…”
Section: Gbsmentioning
confidence: 99%
See 1 more Smart Citation